KINERJA PEGAWAI MELALUI KEPUASAN KERJA PADA UNIT KEBERSIHAN DAN PERSAMPAHAN DINAS LINGKUNGAN HIDUP KABUPATEN PEMALANG - Singgih Setiawan; Pratomo Cahyo Kurniawan; Pujiati Pujiati (Magister Manajemen STIE Bank BPD Jateng, 2022)
This study aims to examine the effect of the Work Environment and Direct Financial Compensation on Employee Performance Besides, this study also aims to examine the effect of Job Satisfaction as an intervening variable. To test these variables, the researchers chose the Sanitation and Environmental Services Unit of Pemalang Regency as the object of research. The study was conducted by distributing questionnaires to 182 Sanitation and Waste Unit Employees in the Pemalang District Environmental Agency. Sampling research using Stratified Random Sampling techniques. The results showed that the Work Environment and Direct Financial Compensation had a significant positive effect on the Performance of Employees in the Cleanliness and Solid Waste Unit of the Environmental Agency of Pemalang Regency. But Job Satisfaction as an intervening variable weakens the influence of the Work Environment and Direct Financial Compensation on Employee Performance in the Cleanliness and Solid Waste Unit of the Pemalang District Environmental Office.